INFORMATION MODELLING OF SUSTAINABLE BIOENERGY AND BIOFUEL PRODUCTION - Deliyska, Boriana; Ivanova, Adelina; Nikolov, Nikolay; Popova-Terziyska, Radostina (Innovation in Woodworking Industry and Engineering design, 2024)
The European Union's Circular Economy project aims to protect the environment and reduce dependence on raw materials. The present study examines the state and the perspective of the sustainable production and use of bioenergy and biofuels as key factors in the realization of a circular economy. For this purpose, an information model is presented. The methodology for building such a model includes a definition of target, scope and users; a generalized scheme of an information system for maintenance of criteria and certificates for sustainability of bioenergy and biofuel production; consideration of software platforms and resources for implementation and publication of the information model. On the base of the generalized schema, a prototype information system is developed consisting of a user interface, functional scripts and a database of bioenergy and biofuel production in Bulgaria. The analysis of data shows the necessity of developing unified standards and classifiers to resolve inconsistencies between bioenergy/biofuel production datasets in all European Union countries.The report has been developed under the activities of project НИС-Б-1279/19.10.2023 at University of Forestry, Bulgaria.